Air quality analysis of nitrogen oxides and relationships with ozone pollution - Wang, Zixian (Kansas State University, 2020)
Air pollution can harm us when it accumulates in the air in high enough concentrations. Nitrogen oxides (NOx), especially nitrogen dioxide (NO₂), are increasingly of concern due to the environmental and health problems they cause. This reviews the recent literature on the reasons and impacts of NOx pollution as well as ozone pollution related to NOx emissions. A review of the impacts of transportation is provided as it pertains to various types of NOx pollution. To improve the air quality, the recent research focuses on how suitable monitoring methods can be used to more economically and precisely collect data on pollution concentrations. Multiple researchers have explored low-cost monitors. Other research explores more convenient ways to eliminate NOx pollution to improve air quality. Regarding the impact of transportation on NOx emissions, vehicle emission technologies are of concern to an increasing number of people, such as using urea to reduce NOx emission for diesel vehicles and developing all-electrical vehicles and plug-in hybrid electric vehicles. This research focused on the data analysis of NO₂ and ozone concentrations in Chicago from the SASA project. Other analyses also provided some data for states and cities in the U.S. to show the relationship between NOx and ozone with transportation. Variations of NOx and ozone emissions were explored. First, the hourly variations in NOx and ozone emissions each day were studied. Second, the seasonal variation in NOx and ozone pollution was analyzed. Third, the differences in NOx emissions on working days and weekends were found. The impacts of NOx emissions on the variation in the ozone concentration in the air were discussed. The purpose of this research is to help more people, especially residents in the communities of Chicago, related to the SASA project to realize the hazard of NOx pollutants to humans and the environment, become aware of the importance and urgency of reducing NOx emissions, and provide feasible methods to solve this problem.
Keywords: low-cost monitor; Transportation; ground-level ozone; photochemical reaction; NO2 concentration; diurnal ozone patterns